Carbonate Precipitation through Microbial Activities in Natural Environment, and Their Potential in Biotechnology: A Review - Zhu, Tingting; Dittrich, Maria (Frontiers in Bioengineering and Biotechnology, 2016)
Calcium carbonate represents a large portion of carbon reservoir and is used commercially for a variety of applications. Microbial carbonate precipitation (MCP), a by-product of microbial activities, plays an important metal coprecipitation and cementation role in natural systems. This natural process occurring in various geological settings can be mimicked and used for a number of biotechnology such as metal remediation, carbon sequestration, enhanced oil recovery and construction restoration. In this study, different metabolic activities leading to calcium carbonate precipitation, their native environment, and potential applications and challenges are reviewed.